PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING DALAM PEMBELAJARAN MATEMATIKA KELAS IV SEKOLAH DASAR - Septiana Andeswari; Dudung Amir Sholeh; Linda Zakiyah (Program Studi PGSD Universitas Flores, 2022)
This study was conducted to determine the development and feasibility of learning media student worksheets (LKPD) based on Problem Based Learning in learning mathematics for grade IV elementary schools. The research method used in this study is research and development (Research and Development) which uses four stages of the Borg and Gall research and development model, namely: 1) research and information collecting, 2) Planning, 3) develop preliminary form a product, 4) preliminary field testing 5) main product revision, 6) main field testing 7) operational product revision 8) operational field testing, 9) final product revision, 10) desimination. The result of this research and development is a problem based learning LKPD product in the fourth grade elementary school mathematics learning. The feasibility level based on the results of the percentage assessment of material experts, learning media experts, and linguists respectively got 90.47%, 82.28%, and 73.3% with the criteria of